Solve for x square root of 3x-8-4=0

Math
3x-8-4=0
Add 4 to both sides of the equation.
3x-8=4
To remove the radical on the left side of the equation, square both sides of the equation.
3x-82=42
Simplify each side of the equation.
Tap for more steps…
Multiply the exponents in ((3x-8)12)2.
Tap for more steps…
Apply the power rule and multiply exponents, (am)n=amn.
(3x-8)12⋅2=42
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
(3x-8)12⋅2=42
Rewrite the expression.
(3x-8)1=42
(3x-8)1=42
(3x-8)1=42
Simplify.
3x-8=42
Raise 4 to the power of 2.
3x-8=16
3x-8=16
Solve for x.
Tap for more steps…
Move all terms not containing x to the right side of the equation.
Tap for more steps…
Add 8 to both sides of the equation.
3x=16+8
Add 16 and 8.
3x=24
3x=24
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3x=24 by 3.
3×3=243
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3×3=243
Divide x by 1.
x=243
x=243
Divide 24 by 3.
x=8
x=8
x=8
Solve for x square root of 3x-8-4=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top